MYOFASCIAL RELEASE AS A MEANS OF INCREASING THE POWER CAPABILITIES OF POWERLIFTERS - Korichko A.V. ,; Samoilov V.V. , (Theory and Practice of Physical Culture, 2023)
Objective of the study was to increase the effectiveness of the training process of beginner powerlifters through the use of myofascial release exercises. Methods and structure of the study. Beginner powerlifters aged 17-18 took part in the pedagogical experiment. The study was conducted on the basis of the Sports School "Olimp" in the village of Novoagansk. The program of training sessions, in addition to basic strength exercises, included myofascial release exercises to increase the flexibility and elasticity of the leading muscle groups of powerlifters. To determine the effectiveness of the proposed training program, the surveyed contingent analyzed the level of their strength capabilities. Results and conclusions. The analysis of the obtained results indicates an increase in the strength capabilities of the study group in the control exercises: in the bench press on a horizontal bench, positive statistically significant changes in strength indicators were found by an average of 11 kg (p <0.05), in the squat with a barbell on the shoulders in on average, strength indicators increased by 14 kg, and in the deadlift, powerlifters improved their results by an average of 8 kg, with maximum shifts in strength parameters in the considered exercises by 17 kg (p <0.05). Thus, the use of myofascial release exercises in the training sessions of beginner powerlifters, in addition to basic exercises (squats with a barbell on the shoulders, bench press, deadlift), myofascial release exercises, is an effective additional means of increasing their strength capabilities.